Lending standards, productivity and credit crunches - Jonathan M. Swarbrick (Bank of Canada, 2019)
We propose a macroeconomic model in which adverse selection in investment drives the amplification of macroeconomic fluctuations, in line with prominent roles played by the credit crunch and collapse of the asset-backed security market in the financial crisis. Endogenous lending standards emerge due to an informational asymmetry between borrowers and lenders about the riskiness of borrowers. By using loan approval probability as a screening device, banks ration credit following financial disturbances, generating large endogenous movements in total factor productivity, explaining why productivity often falls during crises. Furthermore, the mechanism implies that financial instability is heightened when interest rates are low.
Keywords: E22; E32; E44; G01; 330; Credit and credit aggregates; Business fluctuations and cycles; Interest rates; Financial stability; Financial markets; Productivity